The first case of monkeypox virus infection detected in Taiwan: awareness and preparation. (September 2022) - Yang, Zih-Syuan; Lin, Chih-Yen; Urbina, Aspiro Nayim; Wang, Wen-Hung; Assavalapsakul, Wanchai; Tseng, Sung-Pin; Lu, Po-Liang; Chen, Yen-Hsu; Yu, Ming-Lung; Wang, Sheng-Fan
Highlights: The first case of monkeypox virus (MPXV) infection detected in Taiwan was reported on June 24, 2022. Taiwanese population born before 1979 had received the smallpox vaccine. Vaccination and antiviral drugs are necessary for potential monkeypox outbreaks. The imported MPXV contains 51 single nucleotide polymorphisms and phylogenetically clusters with the European isolates. ABSTRACT: Objectives: Monkeypox has recently been detected outside African countries. This study aimed to report and analyze the first case of monkeypox virus infection in Taiwan. Methods: The global epidemiological information was collected from the World Health Organization (WHO) and US Centers for Disease Control and Prevention (CDC). The data from the first confirmed Taiwanese monkeypox case was obtained from Taiwan Centers for Disease Control. Monkeypox diagnosis and prevention strategies were obtained from WHO guidelines on monkeypox. Phylogenetic tree analysis and sequence alignment and comparison were used to identify the phylogeny and single nucleotide polymorphism (SNP) characterization. Results: Epidemiological data indicated that since 2013, monkeypox has caused outbreaks outside African countries through contact with infected animals and international travels. Recently, two confirmed monkeypox cases were reported in Singapore and South Korea. On June 24, 2022, Taiwan CDC reported the first confirmed case of monkeypox virus infection in a 20-year-old man who returned from Germany, from January to June 2022. This is the third confirmed case of an imported monkeypox infection in Asia. Phylogenetic analysis demonstrated that this imported monkeypox virus belonged to the West African clade and is clustered with the 2022 European outbreak monkeypox isolates. Full-length sequence analysis indicates that this virus contains 51 SNPs, and has five variant SNPs compared with the recent outbreak strains. Conclusion: This study suggests that active surveillance, enhancing border control, and the development of vaccines and antiviral drugs are urgently required to prevent and control the burden of monkeypox disease.